DELAMINATION OF COMPOUND MATERIALS LAMINATED BECAUSE OF MACHINING - Damian Escoto, Noemi; Ramírez Elías, Víctor Alfonso (JÓVENES EN LA CIENCIA, 2018)
The necessary methodology for the study of the delamination of laminated composite materials was to developed, starting with the practice of manufacture of the laminated compounds so finally, performing an analysis of the experimental data obtained in the inspection of laminated specimens.